A VISÃO DOS PAIS SOBRE A ATUAÇÃO DA ESCOLA EM ASSUNTOS RELATIVOS À SEXUALIDADE : THE PARENTS' VISION ON THE SCHOOL'S ACTIVITIES IN SUBJECTS RELATED TO SEXUALIDADE (Revista Contexto & Educação, 2021)
The article aims to identify the parents' views of the sixth year students of a State College of a Brazilian municipality, regarding the interventions of the school, related to the manifestations of sexuality by the students. In the data collection, four problem situations were presented to stimulate the reflection of the participants, using situations based on facts that occur daily in schools. The responses were separated and analyzed in categories. It is concluded that the participants present fears and disagreements about the approach of the school, in each case. It is considered that the lack of consensus of the participants, part of the lack of information on the importance of the dialogue around sexuality
Keywords: Family, Sexual Education, School